Hubungan Produk Tahu dan Tempe dalam Optimalisasi Laba (Keuntungan Maksimum) pada UD Wahyu di Kota Denpasar - ABIDIN, AHMAD MAULA; WIDYANTARA, I WAYAN; AMBARAWATI, I GUSTI AGUNG AYU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.1, Januari 2018DO - 10.24843/JAA.2018.v07.i01.p17, 2018)
Relationship of Products Tofu and Tempeh for the Optimization of Profits (Maximum Profits) at UD Wahyu in Denpasar City UD Wahyu is one of the largest industry tofu and tempeh in Denpasar, proved by its ability of the average monthly production reached 167.36 tons of tofu and 51.76 tons of tempeh. Problem faced by UD Wahyu is the selling price of tofu and tempeh remain the same every year and uncertain incurred costs causing change profits over time. The purposes of the research are to determine the production relationship between tofu and tempeh and to find out the optimal production of tofu and tempeh by UD Wahyu. Data collected by in-depth interview to the owner and observation to the local site of production. Data analysis techniques was using regression and maximum profit analysis by the marginal cost approach. The results showed that production relationship between tofu and tempeh is complementary. It means that any increase of tofu production will be followed by an increase in tempeh production. The optimal monthly production of tofu amounted to 69.582 tons and the optimal production of tempeh every month prevailed into two options, amounted to 32.3073 tons and 43.9101 tons respectively. Profits earned by UD Wahyu from production of 32.073 tons tempeh and 69.582 tons tofu between Rp 44.618.449 and Rp 147.989.431. While profits earned by UD Wahyu production of tempeh 43.9101 tons and tofu 69.582 tons between Rp 112.318.141 and Rp 215.689.123. Average production of tofu and tempeh at UD Wahyu every month still exceeds the optimal production. To control costs, UD Wahyu is recommended to work on the optimal production.